Labour standards and regulation in global value chains: The case of the New Zealand Fishing Industry. (October 2016) - Stringer, Christina; Hughes, Steve; Whittaker, D Hugh; Haworth, Nigel; Simmons, Glenn
Building on the concept of polarity in global value chains, we explore how the nature of the governance of a global value chain can evolve and how contingencies can reshape governance arrangements. A case-study of the New Zealand fishing industry highlights how parties inside and outside the global value chain came to contest labour standards, laying the base for credible regulation. In 2011 through a series of convergent events, migrant crew on board South Korean fishing vessels, hitherto exploited, abused and isolated, emerged as a significant actor to bring about a clear transition in the governance of a multipolar global value chain. In this paper, we analyse the series of events which led to regulatory change and consider whether the dynamics from the case offer lessons for improving labour standards and regulation in global value chains more generally.